Evaluating the relationship between drinking behaviour and hydration in competitive cyclists - Sadli, Shahizad Hakimi; Ismail, Zulkifli; Kamaruddin, Harris Kamal; Abu Bakar, Al-Hafiz; Zaker, Nur Amirah; Jamaludin, Masshera (Universiti Teknologi MARA, Perlis, 2025)
Optimal hydration is crucial for high-performance athletes' performance, recovery, and thermoregulation. Despite the recognized importance of fluid balance, limited data exist on hydration behaviours specifically on the objective assessments among elite cyclists in Malaysia. This study investigates the hydration status and fluid intake behaviours among the Selangor State Cycling Team cyclists. Nineteen high-performance cyclists completed a structured questionnaire assessing total water intake (TWI), total fluid loss (TFL), water balance (WB), and the Fluid Behaviour Index (FBI). Descriptive statistics demonstrate a mean TWI of 3,847.45 ± 324.79 ml, a mean TFL of 3,514.43 ± 284.86 ml, and a positive WB of 333.02 ± 254.50 ml. Correlation analyses revealed a weak, nonsignificant positive relationship between FBI and TWI (r = .146, p = .550), as well as a weak, nonsignificant negative relationship between FBI and TFL (r = –.166, p = .496). These findings indicate that self-reported hydration behaviour is not a significant predictor of hydration status in this study. The absence of significant associations underscores the multifactorial nature of hydration regulation and suggests that behavioural indices alone may not adequately reflect individual hydration needs. Future research should incorporate objective physiological markers, as well as psychological and environmental variables, to achieve a comprehensive understanding of hydration determinants in competitive cycling.